2022
DOI: 10.1002/kjm2.12523
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA MIR17HG promotes the proliferation, migration, and invasion of retinoblastoma cells by up‐regulating HIF‐1α expression via sponging miR‐155‐5p

Abstract: Long non‐coding RNA (lncRNA) miR‐17‐92a‐1 cluster host gene (MIR17HG) is oncogenic in several cancers. This study was aimed to probe into its expression characteristics and biological functions in retinoblastoma (RB) and to explore its role in regulating microRNA‐155‐5p (miR‐155‐5p) and hypoxia‐inducible factor‐1α (HIF‐1α). In this study, paired RB samples were collected, and expression levels of MIR17HG, miR‐155‐5p, and HIF‐1α were examined by quantitative real‐time polymerase chain reaction (qRT‐PCR); the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
(65 reference statements)
1
5
0
Order By: Relevance
“…Furthermore, MIR17HG enhanced the gene and protein expression of HIF-1α in RB cells. Taken together, this study suggested the oncogenic effects of MIR17HG in RB mediated through the miR-155-5p/HIF-1α axis (Yan et al, 2022).…”
Section: Long Non-coding Rnas and Retinoblastomasupporting
confidence: 56%
See 1 more Smart Citation
“…Furthermore, MIR17HG enhanced the gene and protein expression of HIF-1α in RB cells. Taken together, this study suggested the oncogenic effects of MIR17HG in RB mediated through the miR-155-5p/HIF-1α axis (Yan et al, 2022).…”
Section: Long Non-coding Rnas and Retinoblastomasupporting
confidence: 56%
“…Yan et al (Yan et al, 2022) investigated the role of the lncRNA MIR17HG (miR-17-92a-1 cluster host gene) and its interaction with miR-155-5p and HIF-1α pathway in RB development. qRT-PCR showed that up-regulation of MIR17HG was negatively associated with miR-155-5p expression.…”
Section: Long Non-coding Rnas and Retinoblastomamentioning
confidence: 99%
“…In addition, MIR17HG has been shown to promote CRC progression through miR-17-5p [24]. Further adding to its importance, MIR17HG can also promote the proliferation, migration, and invasion of retinoblastoma cells through up-regulating HIF-1α expression by sponging miR-155-5p [25]. To the best of our knowledge, our study is the frst of its kind to demonstrate a considerable increase in serum MIR17HG levels in MM patients.…”
Section: Discussionmentioning
confidence: 55%
“…MIR17HG was found to promote proliferation, migration, and invasion of RB cells in previous studies 28 . Among cell lines derived from the human retina, the established ARPE‐19 cell line has similar properties to the endogenous retinal pigment epithelium (RPE) and has therefore been used as a model for analyzing RPE expression profiles 29–35 .…”
Section: Discussionmentioning
confidence: 97%